Circulating tumor cells detected using fluid‐assisted separation technique in esophageal squamous cell carcinoma - Choi, Mun Ki; Kim, Gwang Ha; I, Hoseok; Park, Su Jin; Lee, Moon Won; Lee, Bong Eun; Park, Do Youn; Cho, Yoon‐Kyoung (Journal of gastroenterology and hepatology, 2019)
Background and Aim Esophageal squamous cell carcinoma (ESCC) is one of the aggressive gastrointestinal tract cancers. Detection of circulating tumor cells (CTCs) in peripheral blood from patients with various malignancies has been reported to have diagnostic, prognostic, and therapeutic implications. We aimed to evaluate CTCs in patients with ESCC and assess the clinical significance of CTCs in the early diagnosis of ESCC. Methods Peripheral blood samples for CTCs analyses were prospectively obtained from 73 patients with ESCC prior to treatment between March 2015 and June 2018. CTCs were detected using a centrifugal microfluidic system with a new fluid‐assisted separation technique. Blood samples from 31 healthy volunteers were used as controls. Results After creating a receiver operating characteristic curve to determine the optimal CTC threshold to differentiate patients with ESCC from healthy controls, sensitivity and specificity were most optimized at a CTC threshold of two per 7.5 mL of blood. Among 66 subjects with ≥ 2 CTCs per 7.5 mL of blood, 63 (95.5%) had ESCC. Among 38 subjects with < 2 CTCs per 7.5 mL of blood, 28 (73.7%) were healthy controls. When using this threshold, the sensitivity and specificity for differentiating patients with ESCC from healthy controls were 86.3% and 90.3%, respectively. CTC count was associated with tumor–node–metastasis stage, especially lymph node metastasis, but there was no correlation with any other relevant clinicopathologic variable. Conclusions Our results suggest that CTCs detected using fluid‐assisted separation technique could be helpful for early diagnosis of ESCC. Further large‐scale prospective studies are warranted to validate our findings.